2011
DOI: 10.1007/s00234-011-0879-6
|View full text |Cite
|
Sign up to set email alerts
|

Fractional anisotropy and mean diffusivity in the corpus callosum of patients with multiple sclerosis: the effect of physiotherapy

Abstract: The results of the study show that facilitation physiotherapy influences brain microstructure measured by DTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 53 publications
5
57
2
Order By: Relevance
“…Indeed, increment of structural connectivity has been suggested in MS (Li et al, 2013) and related with WM lesion load (He et al, 2009). It can be present at early stages of disease (Fleischer et al, 2016), during recovery from relapses (Théaudin et al, 2012) and after a rehabilitation program (Ibrahim et al, 2011) evidencing dynamic variations of WM. Changes in the number of axons, axon diameter, the packing density of fibers, axon branching, axon trajectories, myelination, glial cell increase in number and size could underlie increased FA (Zatorre et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, increment of structural connectivity has been suggested in MS (Li et al, 2013) and related with WM lesion load (He et al, 2009). It can be present at early stages of disease (Fleischer et al, 2016), during recovery from relapses (Théaudin et al, 2012) and after a rehabilitation program (Ibrahim et al, 2011) evidencing dynamic variations of WM. Changes in the number of axons, axon diameter, the packing density of fibers, axon branching, axon trajectories, myelination, glial cell increase in number and size could underlie increased FA (Zatorre et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have identified structural changes on diffusion tensor imaging as a result of rehabilitation in the context of physiotherapy [42, 43]. Our study attempted to explore the role of myelin in rehabilitation and repair.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of risperidone and ziprasidone to individuals with schizophrenia led to increased cerebral gray matter volume after 28 days of treatment [239] and administration of citalopram to depressed patients increased hippocampal gray matter within 8 weeks [240]. Changes have also been observed in white matter microstructure by DWI; patients with multiple sclerosis showed increases in fractional anisotropy within 2 months of facilitation of physiotherapy [241], depressed patients showed increase in fractional anisotropy with 4 weeks of psychotherapy [242], and patients with obsessive-compulsive disorder showed a reversal of abnormal white matter microstructure after a 12-week course of antidepressant (SSRI) treatment [243]. …”
Section: Biomarkers and Medical Measuresmentioning
confidence: 99%